Qualitative methods for engaging students in performance measurement. Issue 1 (8th January 2018) - Appleton, Leo
Abstract : Purpose: In the modern "student focused" university setting, quality assurance and continual service improvement have become more and more important in the delivery of academic library services. Working in partnership with their students, academic libraries can enable meaningful engagement, through qualitative methods which allow individual students to contribute to performance measurement activities and service development. The purpose of this paper is to discuss how qualitative methods can be used to engage students in the performance measurement activities of academic libraries. Design/methodology/approach: Through a review of relevant literature, discussion around the main themes and some case study examples, this paper illustrates how effective student engagement through qualitative methods can contribute to the quality assurance, performance measurement and ultimate service improvement of academic libraries. Findings: The paper focuses specifically on focus group and reflective methods and also details some elements of user experience (UX) which brings together different qualitative techniques available for academic libraries. The paper concludes with a feature case study which discusses how meaningful student engagement was achieved through a large-scale UX project at the University of the Arts, London. Originality/value: The paper brings together many different discussions around qualitative methods in performance measurement and is original in its discussions around such activity as student engagement initiatives.